Understanding the Moro nation a textual analysis of the Bangsamoro journal - Acasaran, Karen Jane T.
This study is a textual analysis of the six issues (from March 2007 up to March 2011) of the Bangsamoro Journal, a quarterly publication of the Consortium of the Bangsamoro Civil society. The study deals mostly with presenting the photos per issue, on tallying the frequency the genre of articles published, discussing the background of the editorial staff and writers of the articles, and linking the results to the Bangsamoro timeline created by the opponent. Bangsamoro Journal is a print material operated solely by Muslims, who are members of the Consortium of the Bangsamoro Civil Society in different regions in Mindanao. Hence, it is where Bangsamoro people are able to express their sentiments aside from outdated websites. The issues on war, politics, Memorandum of Agreement on Ancestral Domain, peace and development, CBCS/SFK Activities, Bangsamoro (Internal Issues, Human Rights), and personal experiences, appeared to be the relevant topics to the Bangsamoro People, with Peace and Development as the most important one since it has the frequent number of articles published. Thus, the Bangsamoro Journal aims to promote Peace and Development, which represents the voice of the entire Moro Nation.